Crystal structure of CYP199A2, a para-substituted benzoic acid oxidizing cytochrome P450 from Rhodopseudomonas palustris. - Bell, S; Xu, F; Forward, I; Bartlam, M; Rao, Z; Wong, L (2008)
CYP199A2, a cytochrome P450 enzyme from Rhodopseudomonas palustris, oxidatively demethylates 4-methoxybenzoic acid to 4-hydroxybenzoic acid. 4-Ethylbenzoic acid is converted to a mixture of predominantly 4-(1-hydroxyethyl)-benzoic acid and 4-vinylbenzoic acid, the latter being a rare example of CC bond dehydrogenation of an unbranched alkyl group. The crystal structure of CYP199A2 has been determined at 2.0-A resolution. The enzyme has the common P450 fold, but the B' helix is missing and the G helix is broken into two (G and G') by a kink at Pro204. Helices G and G' are bent back from the extended BC loop and the I helix to open up a clearly defined substrate access channel. Channel openings in this region of the P450 fold are rare in bacterial P450 enzymes but more common in eukaryotic P450 enzymes. The channel is hydrophobic except for the basic residue Arg246 at the entrance, which probably plays a role in the specificity of this enzyme for charged benzoates over neutral phenols and benzenes. The substrate binding pocket is hydrophobic, with Ser97 and Ser247 being the only polar residues. Computer docking of 4-ethylbenzoic acid into the active site suggests that the substrate carboxylate oxygens interact with Ser97 and Ser247, and the beta-methyl group is located over the heme iron by Phe185, the side chain of which is only 6.35 A above the iron in the native structure. This binding orientation is consistent with the observed product profile of exclusive attack at the para substituent. Putidaredoxin of the CYP101A1 system from Pseudomonas putida supports substrate oxidation by CYP199A2 at approximately 6% of the activity of the physiological ferredoxin. Comparison of the heme proximal faces of CYP199A2 and CYP101A1 suggests that charge reversal surrounding the surface residue Leu369 in CYP199A2 may be a significant factor in this low cross-activity.